Modelagem de fratura dúctil em colisão de embarcações utilizando modelo de dano de Lemaitre modificado - Martínez Fernández, Jorge Luis (2017)
Over the last 20 years, the study of accidents involving ship collisions and strandings has led to the development of different methodologies, and to simulate numerically the material’s ductile fracture, several failure criteria have been applied. With this perspective, thi3s article considers a new approach for the application of numerical analysis to ship collision and stranding, based on the Continuum Damage Mechanics (CDM), where new internal variables are inserted in the material constitutive equations, related to the damage produced by the stress field. The objective of this thesis is to propose and assess a modification in Lemaitre’s damage model, called Model with Denominator of Damage Function (MDDF), for the prediction of the location and time instant of the material fracture initiation. The implementation of the proposed model, using the UMATs subroutines integrated to the LS-DYNA program is also described. To validate the proposed fracture criterion, comparisons are conducted with the experimental results, present in the literature: compression in solid aluminum cylinders, indentation in two steel panels and compression of cruciform aluminum columns. Finally, a methodology is developed to simulate ship collisions using the proposed model as material failure criterion. In these applications the results found with the MDDF were also compared with those obtained by the RTCL, BWH criteria and MALCHER (2011) model. In these comparisons, the results in terms of fracture local and force versus displacement curve were excellent.